Collectivism from Employees' Perspective in the Nepalese Banking Industry - Magar, Manisha Thapa; Bista, Sita; Hamal, Krishna; Nyaupane, Netra Prasad (International Journal of Atharva, 2023)
It is vital to recognize the challenges and possibilities that Nepalese commercial bank workers practice collectivist concepts in their workplaces. It is necessary to investigate methods to employ collectivist ideas to practice understandably. That is why it is significant to assess the practice of collectivism in Nepalese commercial banks. Findings emphasize the participants' tendency for placing importance on the success of the collective, prioritizing the group's interests over individual objectives, and regarding acceptance within the group as a significant factor. Additionally, it signifies a moderate degree of consensus regarding the significance of prioritizing the welfare of the group over individual rewards, as perceived by both employees and managers. No significant correlation was found between demographic factors and the mean (Collectivism) ratings provided by the participants. Overall, these results showed the participants' propensity to value collective achievement, sacrifice personal objectives for the good of the group, and place value on group approval. It also showed a moderate level of agreement between managers and employees on the significance of putting group welfare ahead of individual rewards.